Adaptasi dan Uji Psikometrik Instrumen Academic Burnout Validitas dan Reliabilitas pada Populasi Santri - Imdad Robbani; Khairul Bariyyah; Diniy Hidayatur Rahman (JKI (Jurnal Konseling Indonesia), 2026)
This study aimed to adapt the School Burnout Inventory (SBI) and examine its validity and reliability for use among santri in Islamic boarding schools. A quantitative psychometric survey design was employed involving 170 santri from Pondok Pesantren Al-Falah Sumber Gayam. The adaptation process included translating the SBI into Indonesian and adjusting several operational terms to reflect the pesantren context, particularly by replacing school-related expressions with “activities in the Islamic boarding school.” Data were analyzed using Pearson item-total correlation and Cronbach’s Alpha with JASP software. The results showed that all items had positive and significant item-total correlations, ranging from .503 to .747, with p < .001. The reliability analysis produced a Cronbach’s Alpha coefficient of .839, indicating good internal consistency. These findings suggest that the adapted SBI is valid and reliable for assessing academic burnout among santri. The instrument may be used by guidance and counseling practitioners in Islamic boarding schools as an initial screening tool to identify students at risk of academic burnout.